THE EFFECT OF FRACTIONATED RED BEETROOT JUICE ON PERFORMANCE AND OVERALL HEALTH OF A HIGH-PERFORMANCE ATHLETES - Neteča, Jekaterina; Liepiņa, Inga; Veseta, Una; Babarikins, Dmitrijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Over the past 20 years, nitric oxide has become the turning point in athlete physiology and medical research. It has been observed in scientific studies that there are very different protocols for the use of nitrates (red beetroot juice) and different research methodology and results. The most effective solutions for improving the performance of athletes are still being sought. The purpose of this research is to investigate the performance and overall health of a high-performance athlete after consuming fractionated red beetroot juice. The investigation is a one-case study. The respondent is a high-class athlete - track and field (middle and long distance), 20 years old. Three tests were performed in laboratory conditions with an interval of one week. The first test was without the use of fractionated red beetroot juice, the second test after a single dose, and the third after 7 days of use. The research used an interview of the respondent, cardio pulmonary exercise testing measuring device "Vyntus CPX" with gas analysis on a bike ergometer and determination of blood lactate concentration. In the experiment, the athlete's VO2max improved during each test, after one dose by 9%, and after 7 days of use by 13% from the first test. The physical overall health at the end of the test worsened each time, but in the previous tests, where fractionated red beetroot juice was used, a faster recovery of the athlete's working capacity after exercise was observed.